Plant-extract hydrogel for effective wound healing: Animal model studies - Mallick Choudhury A.; Mandal S.S.; Singh N.K.; Sahu M.; Maiti P. (My University, 2025)
Wound healing is a complex process that involves hemostasis, inflammation, proliferation, and remodeling of the damaged tissue. Ayurvedic drugs have been used for centuries to treat various ailments, including wounds. In this study, a biodegradable polymer hydrogel has been developed by incorporating Panchavalkala, an age-old compound drug having wound-healing potential. Its physicochemical, biocompatibility, anti-bacterial, and wound healing properties have been investigated through in vitro and in vivo experiments. The gel exhibits sustained in vitro release of Panchavalkala till 77 hrs. and good adhesion to the wound site. The in vitro antibacterial assay with S. aureus and E. coli has confirmed its antibacterial effectiveness. The in vitro biocompatibility and cytotoxicity of the formulated gel were evaluated using the NIH-3 T3 cell line, which reveals that the gel is biocompatible and shows no toxicity towards cells up to 3 days. The hydrogel has shown accelerated wound closure within 18 days in contrast to 24 days (for the control group), decreased inflammation, as demonstrated by TNF-α immunohistochemistry, and revealed no damage to major organs in vivo, as confirmed through histology. The clinical trial studies (disbudding experiment) on large animals also demonstrated promising results showing rapid healing of wounds compared to conventional medicine. In contrast, naturally generated wounds have also been cured with hydrogel with different healing kinetics, primarily based on wound size, position, and level of infection. The results suggest that the biodegradable gel comprising the ayurvedic drug is a promising alternative for wound healing. © 2025 Elsevier B.V.